EFFECT OF IRRIGATION REGIMES ON YIELD AND WATER USE EFFICIENCY OF EXTRA-EARLY MAIZE VARIETY IN KANO RIVER IRRIGATION PROJECT - Lawal, Mubarak; Abubakar Oyebode, Muyideen; Jamilu Suleiman, (FUDMA JOURNAL OF SCIENCES, 2020)
A field experiment was conducted to evaluate the effect of irrigation regimes on yield and water use efficiency of maize crop (Zea Mays L.; SAMMAZ 29) under different irrigation scheduling. Randomized Complete Block Design (RCBD) was used and the experiment consisted of three levels of irrigation water application depth of 100%, 75% and 50% replacement of Total Available Water Capacity (TAWC) and three irrigation intervals of 7, 10 and 13 days replicated three times. Irrigation water was applied into each of 0.75 m Ã— 90 m furrow using siphon tube of 7.5 cm diameter and 200 cm length. The results showed that the highest average irrigation water use efficiency was at I10D75% with 0.71 kg/m3 while the least was at I13D50% with 0.41 kg/m3. The highest average crop water use efficiency (CWUE) was at I10D75% with 0.79 kg/m3 while the least was at I13D75% with 0.56 kg/m3. The highest average maize yield was at I7D100% with 3580 kg/ha while the least was at I13D50% with 1200 kg/ha. The study established that irrigation after every 10 days interval with 75% replacement of TAWC using furrow irrigation of 90 m lengths produced the highest crop water use efficiency, thus saving about 48.3% of irrigation water (amounting to 329 mm) with reference to control (I7D100%) which causes a yield reduction of about 19% (amounting to 680 kg/ha). This efficient water usage saved cost and also helps to address the problem of high water table of the study area.